(untitled) (Andamios, Revista de Investigación Social, 2009)
This paper explores the notion of narrative identity related to the Historic Center of Mexico City. According to this category, identity is narratively constructed in an ongoing dialogue with culture, defined by Clifford Geertz as the ensemble of stories we tell ourselves about ourselves. A high number of events that have been incorporated to Mexico’s official history have had this area as their setting, especially the main square. The cultural policies directed in recent years towards the Historic Center of Mexico City provide an adequate case study for the notion of narrative identity applied to heritage.